2019
DOI: 10.5489/cuaj.5930
|View full text |Cite
|
Sign up to set email alerts
|

The management of an extraperitoneal bladder injury associated with a pelvic fracture

Abstract: The management of an extraperitoneal bladder injury associated with a pelvic fracture Case A 26-year-old female was involved in a motor vehicle accident as a belted driver after losing control at highway speeds and rolling multiple times into a ditch. There was a prolonged extrication and due to inclement weather conditions, the patient was unable to be evacuated by air ambulance. She was transferred by EMS to a peripheral hospital before expedited transfer to a tertiary trauma centre was possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…If pelvis open reduction and internal fixation is indicated, bladder repair has been shown to lower hardware infection rates. Intraperitoneal ruptures are generally treated with surgical repair [ 1 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…If pelvis open reduction and internal fixation is indicated, bladder repair has been shown to lower hardware infection rates. Intraperitoneal ruptures are generally treated with surgical repair [ 1 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards, the patient responded well to conservative management without the need for surgical intervention [ 6 ]. Furthermore, it has been documented in the literature that cases of uncomplicated EPBI due to pelvic fractures can be managed conservatively with a large-bore catheter for a three-week duration [ 7 ]. This warrants that management of such uncomplicated cases can be achieved without the necessity to surgically intervene.…”
Section: Discussionmentioning
confidence: 99%
“…French scale) catheter used for 2-3 weeks without surgical intervention is the treatment of choice, as many of these injuries will heal without operative intervention [7,[9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Extraperitoneal injury is usually associated with the posterior bladder wall and fibrous attachments including the pubovesical ligament, puboprostatic fascia in men, superior fascia, and inferior fascia [7]. Although previous data has suggested that conservative care with catheter drainage and follow-up imaging is the treatment of choice, for most injuries for patients with an uncomplicated extraperitoneal injury, the current predictive factors and indication of operative management (OM) of extraperitoneal bladder injury (EBI)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation